Genetically modified foods in China and the United States: A primer of regulation and intellectual property protection - Alice Yuen-Ting Wong; Albert Wai-Kit Chan (Food Science and Human Wellness, 2016)
Food is a basic and personal necessity to human. Safety of food is a prime factor to consider apart from nutrition, quality and cost. Genetically modified (GM) foods first came on the market in 1994. Yet safety, transparency and traceability of GM foods are still under hot debate. Nonetheless, the market of GM foods is huge and attractive. Regulatory affairs and intellectual property (IP) are two critical factors affecting the development and commercial success of a food product. This article will take a look at the GM food technology and regulatory framework for GM foods in China and the United States. This article will also discuss the unique patent issues and non-patent IP tools for safeguarding the technology in these two countries.